El rol del trabajador social en tiempos de pandemia ante el trabajo infantil en la ciudad de Machala - Ramírez Idrovo, Thalia Brigitte (My University, 2021)
Children and adolescents are part of the priority attention group in the constitution of Ecuador, in addition, they make up a social group whose protection is a matter of global interest, both from the Government level and from the level of citizenship in each territory Thus, since the constitution of Ecuador, international instruments, and consequently from the Ecuadorian legislation and public policies, it has been tried to improve the context in which this social group operates, preventing and attending to factors that lead to the emergence of work child, given that such a social phenomenon threatens several of their human rights, deprives them of developing all their potentialities, and affects their physical, psychological and social state. Given this, it is necessary for Social Work to consider the actions and strategies necessary to resume and promote the efforts of society to face this social problem. Therefore, the present research work aims to analyze the role of Social Work in the face of child labor in Machala, from a qualitative approach using research and bibliographic analysis, with a view to establishing a proposal for social intervention to respond to the problem of child labor. child labor, taking into account the new limitations and challenges arising from the current pandemic.
Los niños, niñas y adolescentes son parte del grupo de atención prioritaria en la constitución de Ecuador, además, conforman un grupo social cuya protección es tema de interés a nivel global, tanto desde el nivel Gubernamental como desde el nivel de la ciudadanía en cada territorio, es así que, desde la constitución del Ecuador, instrumentos internacionales, y consecuentemente desde la legislación y las políticas públicas Ecuatorianas se ha pretendido mejorar el contexto en el que se desenvuelve este grupo social, previniendo y atendiendo a factores que acarrean al surgimiento del trabajo infantil, dado que tal fenómeno social atenta contra varios de sus derechos humanos, los priva de desarrollar todas sus potencialidades, y afecta perjudica su estado físico, psicología y social. Ante ello, es necesario que desde el Trabajo Social se planteen las acciones y estrategias necesarias para retomar e impulsar los esfuerzos de la sociedad para enfrentar esta problemática social. Por lo tanto, la presente investigación y ensayo complexivo tiene por finalidad analizar el rol del Trabajo Social ante el trabajo infantil en Machala, desde un enfoque cualitativo utilizando la investigación y análisis bibliográfico, con miras a establecer una propuesta de intervención social para responder al problema del trabajo infantil, tomando en cuenta las nuevas limitaciones y desafíos que derivan de la actual pandemia.
Keywords: INTERVENCION SOCIAL; DERECHO HUMANO; PROTECCION; TRABAJO INFANTIL